Differential gene expression of activating Fcγ receptor classifies active tuberculosis regardless of human immunodeficiency virus status or ethnicity. (11th November 2013) - Sutherland, J. S.; Loxton, A. G.; Haks, M. C.; Kassa, D.; Ambrose, L.; Lee, J.‐S.; Ran, L.; van, D.; Maertzdorf, J.; Howe, R.; Mayanja‐Kizza, H.; Boom, W. H.; et al.
Abstract New diagnostics and vaccines for tuberculosis (TB) are urgently needed, but require an understanding of the requirements for protection from/susceptibility to TB. Previous studies have used unbiased approaches to determine gene signatures in single‐site populations. The present study utilized a targeted approach, reverse transcriptase multiplex ligation‐dependent probe amplification (RT‐MLPA), to validate these genes in a multisite study. We analysed ex vivo whole blood RNA from a total of 523 participants across four sub‐Saharan countries (Ethiopia, Malawi, South Africa, and The Gambia) with differences in TB and human immunodeficiency virus (HIV) status. We found a number of genes that were expressed at significantly lower levels in participants with active disease than in those with latent TB infection (LTBI), with restoration following successful TB treatment. The most consistent classifier of active disease was FCGR1A (high‐affinity IgG Fc receptor 1 (CD64)), which was the only marker expressed at significantly higher levels in participants with active TB than in those with LTBI before treatment regardless of HIV status or genetic background. This is the first study to identify a biomarker for TB that is not affected by HIV status or geo‐genetic differences. These data provide valuable clues for understanding TB pathogenesis, and also provide a proof‐of‐concept for the use of RT‐MLPA in rapid and inexpensive validation of unbiased gene expression findings.